Who's who in naval history : from 1550 to the present - Wilson, Alastair, 1934- (Who's who series., 2004)
This A-Z guide covers the life and careers of over 600 key figures in naval history, from the sixteenth century to the present day. Featuring influential figures from the UK, US and around the world, from the great admirals such as Nelson, to minesweepers, designers and administrators, it is an invaluable guide to those who have shaped naval history.